Citizen science to further precision medicine: from vision to implementation. Issue 1 (3rd December 2019) - Petersen, Carolyn; Austin, Robin R; Backonja, Uba; Campos, Hugo; Chung, Arlene E; Hekler, Eric B; Hsueh, Pei-Yun S; Kim, Katherine K; Pho, Anthony; Salmi, Liz; Solomonides, Anthony; Valdez, Rupa S
Abstract: The active involvement of citizen scientists in setting research agendas, partnering with academic investigators to conduct research, analyzing and disseminating results, and implementing learnings from research can improve both processes and outcomes. Adopting a citizen science approach to the practice of precision medicine in clinical care and research will require healthcare providers, researchers, and institutions to address a number of technical, organizational, and citizen scientist collaboration issues. Some changes can be made with relative ease, while others will necessitate cultural shifts, redistribution of power, recommitment to shared goals, and improved communication. This perspective, based on a workshop held at the 2018 AMIA Annual Symposium, identifies current barriers and needed changes to facilitate broad adoption of a citizen science-based approach in healthcare.